Risk Assessment, Worker Training, Personal Protective Equipment, and Safety Monitoring in Occupational Safety and Health: The Case of the Construction Sector in Bangladesh - Rahman, Shahinur; Nashek, Muntasir Hafij; Aubhi, Rezwan Ul Haque; Sarmin, Shaila; Sharmin, Shadia; Rana, Md. Sohel; Hasnat, Md. Abu (Journal of Posthumanism, 2025)
This study intends to explore how risk assessments with training programs, personal protective equipment (PPE), and monitoring practices affect the occupational health and safety standards for construction workers in Bangladesh. The study uses quantitative methods with 291 participants to conduct hypothesis tests through SEM. Research results indicate that work health safety significantly benefits from risk determinations, training of employees, personal protective equipment (PPE), and rigid supervision systems. Yet, safety awareness acts as a middle link that binds these components. The research produces field-tested solutions available to be used by governmental agencies and other business partners in construction that enhance worker safety and alleviate on-the-job hazards. The study presents clear and actionable methods that help government officials and organizations within construction, combined with industry participants, defend workers and minimize workplace safety hazards.